International Financial Statistics, May 2015. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2015)
This May 2015 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. Quarterly issues of Direction of Trade Statistics (DOTS) provide, for 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The yearbook provides, for the most recent seven years, detailed trade data by country for approximately 184 countries, the world, and major areas. The combined subscription package includes all issues of IFS, DOTS, Government Finance Statistics Yearbook, and Balance-of-Payments Statistics Yearbook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet